Heritage as an affective and meaningful information literacy practice: An interdisciplinary approach to the integration of asylum seekers and refugees. (12th September 2021) - Le Louvier, Kahina; Innocenti, Perla
Abstract: Information studies have identified numerous needs and barriers to the integration of asylum seekers and refugees; however, little emphasis has been placed thus far on their need to keep their own culture, values, and traditions alive. In this work, we use ethnographic constructivist grounded theory to explore the place of heritage in the information experience of people who have sought asylum in the United Kingdom. Based on our findings, we propose to conceptualize heritage as an affective and meaningful information literacy practice. Such conceptualization fosters integration by allowing people to simultaneously maintain their own ways of knowing and adapt to local ones. Our research approach provides scholars with a conceptual tool to holistically explore affective, meaningful, and cultural information practices. This study also reveals implications for policymakers, third sector organizations, and cultural institutions working toward the more sustainable integration of asylum seekers and refugees.